2021
DOI: 10.1080/20473869.2020.1865121
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Ghanaian health system: stories from families of children with intellectual and developmental disabilities

Abstract: This study explored the experiences of families in navigating the Ghanaian health system to address the general health needs of their children with intellectual and developmental disabilities (IDD). The sample involved 22 primary caregivers of children with IDD aged 3-18 years who participated in a semi-structured interview. The interviews were analyzed using the constant comparison analytical method. The findings highlighted key enablers and barriers related to three overarching themes: entry into the health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Consistent with other studies, we found that OOP payments associated with medications and treatments often drain the financial resources of caregivers, forcing them to forego treatments and other health services [47,66]. As prior research indicates, we also found that inadequate health system infrastructure is a barrier to providing healthcare to people living with disabilities [67]. We also found that the necessary equipment for testing and diagnosis of CP was limited in most healthcare settings.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with other studies, we found that OOP payments associated with medications and treatments often drain the financial resources of caregivers, forcing them to forego treatments and other health services [47,66]. As prior research indicates, we also found that inadequate health system infrastructure is a barrier to providing healthcare to people living with disabilities [67]. We also found that the necessary equipment for testing and diagnosis of CP was limited in most healthcare settings.…”
Section: Discussionsupporting
confidence: 86%
“…This can affect the quality of care provided to neonates presenting with jaundice in the study area, if not addressed. Previous studies in Ghana have highlighted the poor attitudinal behaviors of health workers, including nurses and midwives, towards patients of all age groups ( Amponsah et al, 2019 ; Asare et al, 2022 ; Dapaah, 2016 ; Lamptey, 2022 ; Sokoloff et al, 2020 ). For example, Andersen (2004) reported in a study on the differential treatments of patients that most nurses and midwives attend to patients with low level of education unprofessionally compared to persons with higher educational qualifications.…”
Section: Discussionmentioning
confidence: 99%